A non-resonant sandwich type bidirectional stepping piezoelectric actuator driven by oblique two-dimensional trajectory: Design, analysis and experiment evaluation. (1st January 2020) - Wang, Liang; Liu, Yingxiang; Deng, Jie; Tian, Xinqi; Liu, Junkao
Highlights: A bidirectional stepping piezoelectric actuator driven by oblique two-dimensional trajectory is presented. The oblique trajectory is formed by compositing the longitudinal and bending deformations of the actuator. The maximum output forces are over 31 N along forward and backward directions. The displacement resolutions along two directions are tested as 24 nm and 25 nm. The forward and backward velocities are over 150 μm/s under voltage of 210 Vp-p . Abstract: This work proposed a non-resonant sandwich type bidirectional stepping piezoelectric actuator driven by an oblique two-dimensional trajectory. This trajectory was formed on the driving tip by compositing the longitudinal deformation of a PZT stack and the bending deformation of a PZT_B group. The longitudinal and bending deformations were employed to press and drive the runner, respectively. The configuration of the actuator was exhibited and its principles were illustrated. A static model of the bending deformation of this actuator was built. Finite element method was used to analyze the motion trajectory of driving tip. A prototype was fabricated to verify the feasibility and evaluate the output characteristics. Experiments denoted that the proposed actuator had coincident characteristics along forward and backward directions. The forward and backward velocities were tested as 154.2 μm/s and 152.7 μm/s when the voltages of PZT_B group and PZT stack were 210 Vp-p and 210 V0-p, respectively. The maximum output forces were tested as about 31.6 N and 31 N along two directions. The tested results also indicated that the proposed actuator could output precision motions with the minimum step sizes of 24 nm and 25 nm along forward and backward directions, respectively.